Surgery for Osteoporotic Fractures - Leung, Frankie; Lau, Tak Wing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This book introduces recent advances in implants and surgical techniques for osteoporotic fractures. It covers most frequent fractures especially in the geriatric population, such as fractures of the hip, distal radius, proximal humerus, peri-prosthetic fractures and drug associated atypical femoral fractures, etc. The book details special surgical techniques which are required to treat these challenging and complex fractures. It also covers the current concept of geriatric fracture care and encompasses the holistic management of these patients from surgical management of the fracture to rehabilitation and prevention of subsequent fragility fractures.
Fracture healing in osteoporotic bone -- Biomechanics of osteoporotic fracture fixation -- Peri-operative management of geriatric patients -- Choice of management and techniques of proximal humeral fixation -- Geriatric elbow fractures and dislocations -- Management of distal radius fractures in the elderly population -- Osteoporotic pelvic fractures including insufficiency fractures -- Management of femoral neck and per-trochanteric fractures including new technology -- Sub-trochanteric fractures including bisphosphonate associated atypical fractures -- Femoral shaft and distal femur including periprosthetic fractures -- Proximal tibial fractures.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Orthopedic surgery; Orthopedics; Surgical Orthopedics; Orthopaedics